Analisis Sektor Basis Infrastruktur sebagai Pemulihan Perekonomian Provinsi Jawa Tengah Akibat Pandemi Covid-19 - Ageng Widodo (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2022)
The COVID-19 pandemic has a major impact on life, not only causing a health and humanitarian crisis, the COVID-19 pandemic affects an economic crisis and an increase in poverty in various countries. A holistic policy of handling the pandemic is needed, both in the field of health and economic recovery. Based on previous studies, the infrastructure sector has an effect on economic development and is allegedly a potential sector for the economy of the province of Central Java. This study aims to analyze the impact of the COVID-19 pandemic on the economy and to determine sector linkages. infrastructure to the structure of the economy to then produce recommendations for economic recovery in the province of Central Java. The results of this study show that the COVID-19 pandemic has an impact on the economy of Central Java province, and there is a link between the infrastructure sector and the economic structure, so that the infrastructure sector is a potential sector in the context of economic recovery in Central Java province in the COVID-19 pandemic situation.